Climate flickers and range shifts of reef corals. Issue 6 (1st August 2004) - Precht, William F.; Aronson, Richard B.
Abstract : Staghorn coral (Acropora cervicornis ) and elkhorn coral (Acropora palmata ), are important reef builders in the Caribbean. In the early to middle Holocene (10 000–6000 years ago), when sea temperatures were warmer than today, Acropora ‐dominated reefs were common along the east coast of Florida as far north as Palm Beach County. The fossil record shows that the northern limits of these two cold‐sensitive species subsequently contracted to Biscayne Bay, south of Miami, apparently as a result of climatic cooling. This response of theAcropora species to climate provides a context for interpreting recent shifts in their geographic distribution. Despite recent disease‐induced mass mortalities throughout the Caribbean and western Atlantic, the two species are now re‐expanding their ranges northward along the Florida Peninsula and into the northern Gulf of Mexico, coincident with increasing sea temperatures. In the face of continued global warming, the northernmost limit of this range expansion will ultimately be determined by a combination of temperature and other physical constraints.